218k views
3 votes
Please help! Somehow not getting the right answer (I checked through the graphs and they’re different)

Please help! Somehow not getting the right answer (I checked through the graphs and-example-1

1 Answer

6 votes

Answer:

see explanation

Explanation:

3 cosx - 4 sinx = rcos(x + α) = rcosxcosα - rsinxsinα

Compare like terms on both sides

3 = rcosα and 4 = rsinα

r =
√(3^2+4^2) =
√(9+16) =
√(25) = 5

tanα =
(sin\alpha )/(cos\alpha ) =
(4)/(3) and in first quadrant, thus

α =
tan^(-1)(
(4)/(3)) ≈ 53.13°

Hence

3cosx - 4sinx = 5cos(x + 53.13)°

User Chirag Ingde
by
5.8k points